We know that:
![(x-a)^2+(y-b)^2=r^2](https://tex.z-dn.net/?f=%28x-a%29%5E2%2B%28y-b%29%5E2%3Dr%5E2)
is an equation of a circle.
When we substitute x and y (from the pairs we have), we'll get a system of equations:
![\begin{cases}(-1-a)^2+(2-b)^2=r^2\\(0-a)^2+(1-b)^2=r^2\\(-2-a)^2+(-1-b)^2=r^2\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7D%28-1-a%29%5E2%2B%282-b%29%5E2%3Dr%5E2%5C%5C%280-a%29%5E2%2B%281-b%29%5E2%3Dr%5E2%5C%5C%28-2-a%29%5E2%2B%28-1-b%29%5E2%3Dr%5E2%5Cend%7Bcases%7D)
and all we have to do is solve it for a, b and r.
There will be:
![\begin{cases}(-1-a)^2+(2-b)^2=r^2\\(0-a)^2+(1-b)^2=r^2\\(-2-a)^2+(-1-b)^2=r^2\end{cases}\\\\\\ \begin{cases}1+2a+a^2+4-4b+b^2=r^2\\a^2+1-2b+b^2=r^2\\4+4a+a^2+1+2b+b^2=r^2\end{cases}\\\\\\ \begin{cases}a^2+b^2+2a-4b+5=r^2\\a^2+b^2-2b+1=r^2\\a^2+b^2+4a+2b+5=r^2\end{cases}\\\\\\ ](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7D%28-1-a%29%5E2%2B%282-b%29%5E2%3Dr%5E2%5C%5C%280-a%29%5E2%2B%281-b%29%5E2%3Dr%5E2%5C%5C%28-2-a%29%5E2%2B%28-1-b%29%5E2%3Dr%5E2%5Cend%7Bcases%7D%5C%5C%5C%5C%5C%5C%0A%5Cbegin%7Bcases%7D1%2B2a%2Ba%5E2%2B4-4b%2Bb%5E2%3Dr%5E2%5C%5Ca%5E2%2B1-2b%2Bb%5E2%3Dr%5E2%5C%5C4%2B4a%2Ba%5E2%2B1%2B2b%2Bb%5E2%3Dr%5E2%5Cend%7Bcases%7D%5C%5C%5C%5C%5C%5C%0A%5Cbegin%7Bcases%7Da%5E2%2Bb%5E2%2B2a-4b%2B5%3Dr%5E2%5C%5Ca%5E2%2Bb%5E2-2b%2B1%3Dr%5E2%5C%5Ca%5E2%2Bb%5E2%2B4a%2B2b%2B5%3Dr%5E2%5Cend%7Bcases%7D%5C%5C%5C%5C%5C%5C%0A)
From equations (II) and (III) we have:
![\begin{cases}a^2+b^2-2b+1=r^2\\a^2+b^2+4a+2b+5=r^2\end{cases}\\--------------(-)\\\\a^2+b^2-2b+1-a^2-b^2-4a-2b-5=r^2-r^2\\\\-4a-4b-4=0\qquad|:(-4)\\\\\boxed{-a-b-1=0}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Da%5E2%2Bb%5E2-2b%2B1%3Dr%5E2%5C%5Ca%5E2%2Bb%5E2%2B4a%2B2b%2B5%3Dr%5E2%5Cend%7Bcases%7D%5C%5C--------------%28-%29%5C%5C%5C%5Ca%5E2%2Bb%5E2-2b%2B1-a%5E2-b%5E2-4a-2b-5%3Dr%5E2-r%5E2%5C%5C%5C%5C-4a-4b-4%3D0%5Cqquad%7C%3A%28-4%29%5C%5C%5C%5C%5Cboxed%7B-a-b-1%3D0%7D%20)
and from (I) and (II):
![\begin{cases}a^2+b^2+2a-4b+5=r^2\\a^2+b^2-2b+1=r^2\end{cases}\\--------------(-)\\\\a^2+b^2+2a-4b+5-a^2-b^2+2b-1=r^2-r^2\\\\2a-2b+4=0\qquad|:2\\\\\boxed{a-b+2=0}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Da%5E2%2Bb%5E2%2B2a-4b%2B5%3Dr%5E2%5C%5Ca%5E2%2Bb%5E2-2b%2B1%3Dr%5E2%5Cend%7Bcases%7D%5C%5C--------------%28-%29%5C%5C%5C%5Ca%5E2%2Bb%5E2%2B2a-4b%2B5-a%5E2-b%5E2%2B2b-1%3Dr%5E2-r%5E2%5C%5C%5C%5C2a-2b%2B4%3D0%5Cqquad%7C%3A2%5C%5C%5C%5C%5Cboxed%7Ba-b%2B2%3D0%7D)
Now we can easly calculate a and b:
![\begin{cases}-a-b-1=0\\a-b+2=0\end{cases}\\--------(+)\\\\-a-b-1+a-b+2=0+0\\\\-2b+1=0\\\\-2b=-1\qquad|:(-2)\\\\\boxed{b=\frac{1}{2}}\\\\\\\\a-b+2=0\\\\\\a-\dfrac{1}{2}+2=0\\\\\\a+\dfrac{3}{2}=0\\\\\\\boxed{a=-\frac{3}{2}}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7D-a-b-1%3D0%5C%5Ca-b%2B2%3D0%5Cend%7Bcases%7D%5C%5C--------%28%2B%29%5C%5C%5C%5C-a-b-1%2Ba-b%2B2%3D0%2B0%5C%5C%5C%5C-2b%2B1%3D0%5C%5C%5C%5C-2b%3D-1%5Cqquad%7C%3A%28-2%29%5C%5C%5C%5C%5Cboxed%7Bb%3D%5Cfrac%7B1%7D%7B2%7D%7D%5C%5C%5C%5C%5C%5C%5C%5Ca-b%2B2%3D0%5C%5C%5C%5C%5C%5Ca-%5Cdfrac%7B1%7D%7B2%7D%2B2%3D0%5C%5C%5C%5C%5C%5Ca%2B%5Cdfrac%7B3%7D%7B2%7D%3D0%5C%5C%5C%5C%5C%5C%5Cboxed%7Ba%3D-%5Cfrac%7B3%7D%7B2%7D%7D)
Finally we calculate
![r^2](https://tex.z-dn.net/?f=r%5E2)
:
![a^2+b^2-2b+1=r^2\\\\\\\left(-\dfrac{3}{2}\right)^2+\left(\dfrac{1}{2}\right)^2-2\cdot\dfrac{1}{2}+1=r^2\\\\\\\dfrac{9}{4}+\dfrac{1}{4}-1+1=r^2\\\\\\\dfrac{10}{4}=r^2\\\\\\\boxed{r^2=\frac{5}{2}}](https://tex.z-dn.net/?f=a%5E2%2Bb%5E2-2b%2B1%3Dr%5E2%5C%5C%5C%5C%5C%5C%5Cleft%28-%5Cdfrac%7B3%7D%7B2%7D%5Cright%29%5E2%2B%5Cleft%28%5Cdfrac%7B1%7D%7B2%7D%5Cright%29%5E2-2%5Ccdot%5Cdfrac%7B1%7D%7B2%7D%2B1%3Dr%5E2%5C%5C%5C%5C%5C%5C%5Cdfrac%7B9%7D%7B4%7D%2B%5Cdfrac%7B1%7D%7B4%7D-1%2B1%3Dr%5E2%5C%5C%5C%5C%5C%5C%5Cdfrac%7B10%7D%7B4%7D%3Dr%5E2%5C%5C%5C%5C%5C%5C%5Cboxed%7Br%5E2%3D%5Cfrac%7B5%7D%7B2%7D%7D)
And the equation of the circle is:
Answer:
Its B
Step-by-step explanation:
I calculated it using the formula and got B
Answer:
a = 4
Step-by-step explanation:
a^2 + b^2 = c^2
a= ?
b= 3
c= 5 (c is always the hypotenuse)
*plug in given values
a^2 + 3^2 = 5^2
a^2 + 9 = 25
-9 -9
a^2 = 16
*find the square root
sqrt(a) = sqrt(16)
a = 4
Answer:
48y⁶w¹¹
Step-by-step explanation:
[-3y⁵][4y] → -12y⁶
×
[w³][-4w⁸] → -4w¹¹
______
48y⁶w¹¹
I am joyous to assist you anytime.
Answer:
=18fx+35gx
Step-by-step explanation:
I think.. Ask your teacher if it's right have a good day :)